Aplikasi Penilaian Kinerja Dosen pada Proses Belajar Mengajar Berbasis Web: Studi Kasus di Badan Penjamin Mutu Internal Institut Teknologi Padang - Harison Son; Roby Faisal (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
The lecturer has the main duty of Tridharma of Higher Education, namely education, research and community service. Currently, the assessment of lecturers using questionnaires by students at the Padang Institute of Technology is still ineffective and the data is less valid. With this application, the internal quality assurance agency of Padang Technology Institute will not be bothered to calculate student questionnaire data as much as 2500 people. The results of this application provide a detailed value to the lecturer, in which a lecturer has a low score and in which part a lecturer excels based on the question items. This value will be calculated by the application of each student who has filled the questionnaire. The application will provide information on the value of the whole lecturer and can be the basis to make improvements to the weakness of the lecturer in detail and accurately. This application is designed using PHP programming language and MySql database. Lecturer performance appraisal results can be obtained directly, to determine the highest to lowest score and can also see the results of the overall lecturer's score accessed on the account of each lecturer on the campus information system.